Identification and Classification of Alzheimer’s Disease Patients Using Novel Fractional Motion Model - Du, Lei; Xu, Boyan; Zhao, Zifang; Han, Xiaowei; Gao, Wenwen; Shi, Sumin; Liu, Xiuxiu; Chen, Yue; Wang, Yige; Sun, Shilong; Zhang, Lu; Gao, Jiahong; et al. (Frontiers in Neuroscience, 2020)
Most of diffusion MRI (dMRI) techniques use the mono-exponential model to describe the diffusion process of water in the brain. However, the observed dMRI signal decay curve deviates from the mono-exponential form. To solve this problem, the fractional motion (FM) model has been developed, which was regarded to be a more appropriate model for describing the complex diffusion process in brain tissue. It is still unclear in the identification and classification of Alzheimer's disease (AD) patients using the FM model. The purpose of this study was to investigate the potential feasibility of FM model differentiating AD patients from healthy controls and grading patients with AD. Twenty four patients with AD and 11 healthy controls were included. The left and right hippocampus were selected as regions of interest (ROIs). The ADC values and FM-related parameters, including the Noah exponent (α), the Hurst exponent (Η), and the memory parameter (μ=Η-1/α), were calculated and compared between AD patients and healthy controls and between mild AD and moderate AD patients using a two-sample t-test. The correlations between FM-related parameters α, Η, μ, and ADC values and the cognitive functions assessed by mini-mental state examination (MMSE) and Montreal cognitive assessment (MoCA) scales were investigated using Pearson partial correlation analysis in patients with AD. The receiver operating characteristic (ROC) analysis was used to assess the differential performance. We found that the FM-related parameter α could be used to distinguish AD patients from healthy controls (p<0.05) with greater sensitivity and specificity (left ROI, 0.917 and 0.636; right ROI, 0.917 and 0.727) and grade AD patients (p< 0.05) showed higher sensitivity and specificity (right ROI, 0.917, 0.75). The α was found to be positively correlated with MMSE (p<0.05) and MoCA (p<0.05) scores in patients with AD, indicating that the α values in the bilateral hippocampus were a potential MRI-based biomarker of disease severity in AD patients. This novel diffusion model may be useful for further understanding of neuropathologic changes in patients with AD.